Nearshoring in Mexico: Navigating Expectations and Realities of the Reconfiguration of Global Value Chains - Roberto Duran-Fernandez (ZBW - Leibniz Information Centre for Economics, 2024)
This paper critically examines the phenomenon of nearshoring in Mexico within the broader context of global value chain (GVC) reconfiguration. As geopolitical tensions, rising labor costs in Asia, and the push for supply chain resilience have intensified, nearshoring has emerged as a prominent strategy, particularly in Mexico. However, despite the optimistic narratives surrounding nearshoring, this paper argues that its impact on Mexico is more complex and nuanced than often portrayed. By analyzing economic, geopolitical, and environmental factors, the paper evaluates Mexico's positioning to benefit from nearshoring trends. It highlights the opportunities, such as increased foreign direct investment (FDI) and potential GDP growth, while also addressing the significant challenges, including infrastructure deficits and the need for strategic industrial policies. The analysis reveals that the benefits of nearshoring are likely to be concentrated in specific sectors and regions, necessitating a balanced perspective that recognizes both the potential and limitations of this trend. Ultimately, the paper provides a grounded assessment of nearshoring's implications for Mexico, offering insights into the broader narrative of GVC reconfiguration and its localized effects
Keywords: F63; O14; O25; R58; Q56; 330; Nearshoring; Global Value Chains; Economic Development; Industrial Policy